Реологические исследования экологически чистых материалов на основе полимерных и органических отходов - Лебедев, Владимир Владимирович; Карев, Артем Игоревич; Чавров, Сергей Александрович (НТУ "ХПИ", 2012)
Проведены реологические исследования экологически чистых древесно-полимерных материалов на основе отходов полипропилена и органических отходов. В качестве наиболее оптимальных материалов для переработки методами литья под давлением для получения листовых материалов выбраны древесно-полимерные материалы с использованием древесной муки и муки хвои.

Rheological researches of pollution-free wood-polymeric materials on the basis of a waste of polypropylene and an organic waste are carried out. In the capacity of the optimal materials for rehash by methods of pressure casting for production of sheetings wood-polymeric materials with utilisation of a wood flour and a needles flour are chosen.
Rheological researches of pollution-free wood-polymeric materials on the basis of a waste of polypropylene and an organic waste
Keywords: утилизация промышленных отходов; древесно-полимерные материалы; отходы термопластов; реологические исследования; оптимизация; переработка; waste; polymers; wood; rheology; optimisation; rehash